PO084 Atypical presentation of young-onset corticobasal degeneration. (1st December 2017) - Lim, Sze Hway; Mann, David; Plessis, Daniel du; Kobylecki, Christopher
Abstract : A 42 year old female presented with a one year history of gait problems, slowing of movement and intermittent dystonic posturing of her left foot. She was diagnosed with young onset Parkinson's disease and responded well to Levodopa, with early peak dose dyskinesia and motor fluctuations. She later developed behavioural changes in the form of impulsivity, hypersexuality, hoarding behaviours and obsessive thoughts. She died 3 years after diagnosis following a fall which resulted in an acute subdural haemorrhage. Her post mortem histopathology demonstrated pathology in keeping with a hybrid form of tauopathy sharing features of both corticobasal degeneration (CBD) and progressive supranuclear palsy (PSP). Our patient's young age of onset, Levodopa responsiveness and development of dyskinesia are very unusual features of CBD/PSP. Her behavioural abnormalities, initially interpreted as dopamine dysregulation/impulse control disorder, were consistent with behavioural features of frontotemporal dementia seen in degenerative tauopathies. This case exemplifies the challenges in making accurate ante mortem diagnoses given the marked clinical heterogeneity of CBD.